Factors associated with buprenorphine versus methadone use in pregnancy. Issue 4 (1st October 2016) - Krans, Elizabeth E.; Bogen, Debra; Richardson, Gale; Park, Seo Young; Dunn, Shannon L.; Day, Nancy
ABSTRACT: Background: Buprenorphine has recently emerged as a safe and effective treatment option for pregnant women with opioid use disorder (OUD) and is associated with superior neonatal outcomes. This study characterized and compared patient populations who used buprenorphine versus methadone during pregnancy in an academic medical center. Methods: Observational retrospective cohort evaluation of 791 pregnant women with OUD on opioid maintenance treatment from 2009 to 2012. Buprenorphine versus methadone use was defined as use after either (a) conversion from illicit opioid use during pregnancy or (b) ongoing prepregnancy use. Multivariable logistic regression was used to identify patient characteristics predictive of buprenorphine use. Results: Among 791 pregnant women, 608 (76.9%) used methadone and 183 (23.1%) used buprenorphine. From 2009 to 2012, buprenorphine use during pregnancy increased from 10.1% to 33.2%. Pregnant women using buprenorphine were significantly more likely to be older, married, employed, have more education, and have a history of prescription opioid use compared with women using methadone. In contrast, pregnant women using methadone were significantly more likely to have hepatitis C virus infection, use cocaine, benzodiazepines, or marijuana, and have a history of heroin and/or intravenous opioid use. In multivariable analysis, pregnant women who were older (odds ratio [OR] = 1.01; 95% confidence interval [CI]: 1.02, 1.11), were employed (1.87; 1.20, 2.90), and had a history of opioid maintenance treatment prior to pregnancy (2.68; 1.78, 4.02) were more likely to use buprenorphine during pregnancy. Pregnant women with a history of benzodiazepine use (0.48; 0.30, 0.77), who had children no longer in their legal custody (0.63; 0.40, 0.99), and who had a partner with a substance use history (0.37; 0.22, 0.63) were less likely to use buprenorphine during pregnancy. Conclusions: Disparities exist among patients who use buprenorphine versus methadone during pregnancy and indicate the need to improve the availability and accessibility of buprenorphine for many pregnant women.